Bacillus thuringiensis, a remarkable biopesticide - Sena da Silva, Igor Henrique [UNESP]; Mueller de Freitas, Marcelo [UNESP]; Polanczyk, Ricardo Antônio [UNESP] (Elsevier, 2021)
The entomopathogenic bacterium Bacillus thuringiensis (Bt) has been studied widely and intensively in terms of isolation and transmission, characterization, mode of action, improved formulations, and compatibility with natural enemies and Bt crops. This knowledge has resulted in the availability of extremely competitive biopesticides, with remarkable selectivity and specificity, on the market. The biopesticide Dipel is available on the worldwide pesticide market since the 1970s and recently had an outstanding performance against the noctuids Helicoverpa armigera and Chrysodeixis includens in Brazilian pest outbreaks. This chapter describes the scientific background that made Bt become the most important microbial control agent in the integration of agricultural pest management with low environmental constrains, with higher efficacy than chemical pesticides.
Keywords: Bt biopesticides; Eco-friendly; IPM systems; Microbial control; Sustainable agriculture